Incomplete homicide-suicide in Hunan China from 2010 to 2019: characteristics of surviving perpetrators - Qiaoling Sun (BMC, 2021)
Abstract Background The mental and psychological conditions of the individuals involved in homicide followed by suicide (H-S) are still unclear, especially in China. Information on these aspects cannot be accurately obtained due to the death of perpetrators. This study aims to demonstrate the characteristics of incomplete H-S with surviving perpetrators, which provide the possibility to obtain detailed mental and psychological information. Methods This study explores incomplete H-S events occurred in Hunan, China from 2010 to 2019, in which the surviving perpetrators received a forensic psychiatric assessment. Three aspects of information, i.e., the subject’s demographic, clinical and criminal information, were recorded and analysed. Results 125 incomplete H-S incidents involved 166 victims were found in the current study. A total of 112 (89.6%) perpetrators were diagnosed with mental disorders, but only 56 of them had a history of consultation due to mental problems, and only one of them adhered to treatment. In most cases, the motivation is related to the psychopathological states, with the most common diagnosis being major depression, followed by schizophrenia. Gender difference was significant among the subjects: females were more likely to have a suicidal history, to be diagnosed as major depression and to be motivated by delirious altruism and family problems. Conclusions This study indicated that psychopathology might be a predisposing factor, which highlighted the importance of mental state assessment for the population involved in incomplete H-S. A clearer understanding of the role of mental disorders might be helpful for the intervention of H-S.